2021
DOI: 10.1038/s41598-021-89516-6
|View full text |Cite
|
Sign up to set email alerts
|

The lower respiratory tract microbiome of critically ill patients with COVID-19

Abstract: COVID-19 infection may predispose to secondary bacterial infection which is associated with poor clinical outcome especially among critically ill patients. We aimed to characterize the lower respiratory tract bacterial microbiome of COVID-19 critically ill patients in comparison to COVID-19-negative patients. We performed a 16S rRNA profiling on bronchoalveolar lavage (BAL) samples collected between April and May 2020 from 24 COVID-19 critically ill subjects and 24 patients with non-COVID-19 pneumonia. Lung mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 26 publications
5
50
0
5
Order By: Relevance
“…A study performed with 24 critically ill COVID-19 patients and 24 non-COVID-19 patients with pneumonia [38] showed taxonomical differences between the lung microbiota of Future research to determine their roles in COVID-19 development and evolution is required.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed with 24 critically ill COVID-19 patients and 24 non-COVID-19 patients with pneumonia [38] showed taxonomical differences between the lung microbiota of Future research to determine their roles in COVID-19 development and evolution is required.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian paper showed bronchoalverolar lavage from 24 critically ill COVID-19 patients tended to grow gram-negative bacteria "predisposed to multidrug resistance" while 24 matched non-COVID-19 controls had more commensal flora such as Haemophilus sp. and streptococci [ 61 ]. Another reported 7 relatively young COVID-19 ICU patients with few comorbidities except obesity harbored carbapenemase-producing Klebsiella pneumoniae [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the lung microbiome in COVID-19-negative pneumonia patients was mainly characterized by the enrichment of Haemophilus influenzae , Veillonella dispar , Granulicatella sp., Porphyromonas sp., and Streptococcus sp. [ 91 ]. Several studies have already reported that respiratory virus infections can alter the microbial composition and total amount of bacterial load [ 21 , 92 ].…”
Section: The Lung Microbiome During Diseasementioning
confidence: 99%
“…Recent studies showed that gut microbiome composition differed significantly among COVID-19 patients compared with non-COVID-19 individuals [ 91 , 92 ]. Besides, plasma concentrations of inflammatory cytokines, chemokines, and tissue damage markers are correlated with gut microbiota composition.…”
Section: The Lung Microbiome During Diseasementioning
confidence: 99%